INOVASI KEPALA SEKOLAH DALAM PEMBELAJARAN TATAP MUKA ERA KEBIASAAN BARU PASCA MASA PANDEMI COVID19 - Reza Aditya Ramadhani Reza; Ahmad Mushthofa; Dila Rukmi Octaviana; Defi Firmansah (STAINU Tasikmalaya, 2022)
Seeing the phenomenon of the covid 19 pandemic that never ends, as an educational institution is also affected, so learning is not so optimal. the principal as a role figure in the school environment in order to continue to exist in PTMT during the new habit of the covid pandemic according to existing rules. The purpose of this research is to describe the role of school principals in implementing limited (PTMT) innovations during the covid 19 pandemic. This research method uses a descriptive qualitative approach with interviews, observation and documentation. The data collection from informants includes school principals, homeroom teachers and teachers. Data analysis techniques through data presentation, data reduction and drawing conclusions. The results of this study indicate that the implementation of face-to-face learning is limited in the era of new habits during the covid 19 pandemic as follows: First, the principal forms a work team with teachers to plan limited face-to-face learning activities in accordance with existing rules and health protocols. Second, the process of implementing the learning process of the principal instructing school residents to apply the 3 M, from washing hands, wearing masks, maintaining distance, PTMT 2 times a week alternately from 50 percent of students. The rest is carried out online by cursing application platforms such as Whatshap, Google Meet. Third, the evaluation by the principal in the learning process certainly does not escape from supporting activities such as providing motivation, training in learning workshops, seminars during the new habitual period.